Population movement, disease, and environment in northwest Zimbabwe, 1950 to 1980 - Mudzimu, A (2023)
This thesis investigates the multi-layered relationships between population movements and African experiences of disease and environment in colonial Gokwe, northwest Zimbabwe. The question I address is how did ideas of disease and environment shape knowledge systems and social relations between 1950 and 1980. Drawing on extensive field research, I make two inter-locking arguments. First, in addition to the more common focus on exchanges between state officials and Africans, which is basically cast as a top-down disciplinary project, I argue that ‘African-African’ interactions were central in producing and reproducing unique knowledge systems. Whilst the colonial state made aggressive interventions into the management of African environment and disease, control of tsetse and mosquitoes, such interventions were variably engaged with, co-opted, and subverted by African populations with different and often clashing ideas about disease. The result was the simultaneous making and remaking of social identities and shifting relations with political authority. Second, I seek to push the consideration of colonial interventions beyond a state concern for ‘ordering diseased’ African spaces through laboratory-like experiments. Using Gokwe as an example, I argue that colonial interventions were elusive, fluid, and abstract force that suffered from external modifications and abuses. Of note here were the counterinsurgency campaigns of the Rhodesian forces in which biological agents were used against guerrillas travelling through Gokwe from Zambia thus introducing radically new experiences and meanings of disease and environment.